The formation of integrated structures as a task of anti-crisis strategy of the real economy - Ortina, Hanna; Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна (My University, 2015)
It is rationalized the directions of forming integratedproduction systems as a task of anti-crisis strategy of the real economy. It is shown that the main directions of anticrisis strategy of development of the real economy include the following: identifying and monitoring the situation of integrated production systems, funding of analytical research on development prospects on the international market, assessment of their impact on social services; forming communication platforms for their members, promoting the exchange of experience; implementation ofprograms to promote the access of participants to foreign markets, conducting joint market research, implementation of an educational policy offorming institutional environment.
Keywords: anti-crisis strategy; development; industry; real economy sector; sustainable development